Arte na educação infantil : uma experiência estética com crianças pequenas - Oliveira, Adélia Pacheco de Freitas (2016)
This research addresses the issue of teaching art in early childhood education and aims to analyze how the experience of playing mediated by an art work image enhances the aesthetic education of young children. The study was conducted with a group of four-year-old children, in a Municipal Kindergarten Centre located in Vitória-ES. It consisted in planning a pedagogical action from the pre-selection, made by the teacher / researcher, of images from artists who portray play. The images were submitted to children’s choice, being enlarged and printed to form a three-dimensional puzzle. As for the methodological procedures, the research is based on qualitative approach, using photography and audio recording to gather the data produced during the play and the children’s imagistic experiences with the toy, which took place in pairs, trios and the whole class. Data analysis established dialogue with authors such as Benjamin (1984; 1987), Barbosa (2014), Barbosa (2009), Schütz-Foerste (2004); Duarte (2001); Vygotsky (2004), Kramer (1996), Ferreira and Sarmento (2008), Agamben (2005), among others. The results showed that it was possible to create favorable conditions to the teaching of art for young children from the play to assemble the puzzle composed of art work images. Thus, it is possible to envision new ways to learn and teach art, because, at the moments when children played, it was provided conditions that favored the aesthetic experience.